The summer of lost letters - Reynolds, Hannah, 1988- (Razorbill, 2021)
The discovery of a packet of old letters sends seventeen-year-old Abby Schoenberg to Nantucket to unravel a family mystery about her grandmother's past, but things get complicated when Abby meets the cute grandson of a prominent family who wants to stop her from investigating.